A SYSTEMATIC APPROACH TO THE FORMATION OF VALEOLOGICAL COMPETENCE OF TEACHERS AND STUDENTS IN SCHOOL CONDITIONS HEALTH CULTURES (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the actual guestions valeological competence of the modern teacher, is explored the structure valeological competence teacer, which is developed on the basis of priority spiritual-valued gualitties teacher, that is deaten back on forming vital jurisdictions undent.